Health and Medical Public Relations - Riggulsford, Myc. 1956- (Abingdon, Oxon : Routledge, 2013)
"Health and Medical Public Relations takes a fresh look at media relations and news values. It examines how information about medical research from the academic, pharmaceutical and charitable sectors is disseminated to target audiences through a variety of PR techniques. Scrutinising a wide range of health-related public relations activities, the book combines a critical, analytical and cultural overview of these methods with helpful guidance on their practical application"--Provided by publisher.
Includes bibliographical reference and index.
Keywords: Health Communication; Public Relations; Communications Media